Islamic Social Finance as Alternative Mechanism for Well-being of the Community: A Bibliometric Analysis - Mohd Yahya bin Mohd Hussin, Zuriadah binti Ismail, Fidlizan bin Muhammad, Azila binti Abdul Razak (Tanjung Malim, 2024)
Islamic Social Finance as Alternative Mechanism for Well-being of the Community: A Bibliometric Analysis by Mohd Yahya bin Mohd Hussin, Zuriadah binti Ismail, Fidlizan bin Muhammad, Azila binti Abdul Razak